Cross-sectional study of reversible airway obstruction in LAM: better evidence is needed for bronchodilator and inhaled steroid use. Issue 10 (30th July 2019) - Johnson, Jan; Johnson, Simon R
Abstract : Lymphangioleiomyomatosis can be associated with reversible airflow obstruction and although no guidelines around reversibility testing or inhaled therapy exist, many patients receive bronchodilators and inhaled corticosteroids. To better identify those who may benefit, we examined bronchodilator reversibility and inhaled therapy in a national cohort of 213 subjects. 20% of those tested had airway reversibility by standard criteria. 55% of patients used 13 different combinations of bronchodilators and inhaled corticosteroids. Increasing inhaler classes were associated with reversibility and more rapid FEV1 decline. Reversibility testing should be performed in all patients and inhaled therapy should be formally studied.